EXPLORING PATENT ACTIVITY AND ITS POTENTIAL ASSOCIATION WITH HEALTHCARE OUTCOMES: A CASE STUDY OF OSTOMY PRODUCTS IN SWEDEN. (28th June 2017) - Calara, Paul Samuel; Althin, Rikard; Inglese, Gary; Nichols, Thomas
Abstract : Objectives: The aim of this study was to evaluate whether ostomy industry patent activity (PA) is associated with patient outcomes and healthcare costs. Methods: Two groups of ostomy pouch users based on manufacturer PA (low or high) were compared in terms of ostomy-related wear patterns, adverse events, and healthcare expenditure. Using Swedish registry data, all patients with newly formed stomas were divided between each group and were followed during a 2-year period (2011–12 ). Propensity score matching and parametric duration analysis were used to compare outcomes between patients of similar characteristics such as sex, age, and ostomy surgery type. Results: In both one- and two-piece systems, the high PA group had significantly lower monthly ostomy-related expenditure than the low PA group (one-piece: 197.47 EUR versus 233.34 EUR; two-piece: 164.00 EUR versus 278.98 EUR). Fewer pouch and skin wafer purchases per month were an important driver of cost differences. Both groups had similar likelihood of purchasing dermatological products for skin complications over time. Conclusions: PA in the ostomy care industry was associated with reduced healthcare costs, but not necessarily with fewer skin complications. It suggests that there is a health economic benefit from products made by patent intensive companies which may differentiate them from generic comparators, but more research is needed to understand the impact of activities conducive to medical innovation on health outcomes.